Designed Enclosure Enables Guest Binding Within the 4200 Å3 Cavity of a Self‐Assembled Cube1. (14th April 2015) - Ramsay, William J.; Szczypiński, Filip T.; Weissman, Haim; Ronson, Tanya K.; Smulders, Maarten M. J.; Rybtchinski, Boris; Nitschke, Jonathan R.
Abstract Metal–organic self‐assembly has proven to be of great use in constructing structures of increasing size and intricacy, but the largest assemblies lack the functions associated with the ability to bind guests. Here we demonstrate the self‐assembly of two simple organic molecules with CdII and PtII into a giant heterometallic supramolecular cube which is capable of binding a variety of mono‐ and dianionic guests within an enclosed cavity greater than 4200 Å3. Its structure was established by X‐ray crystallography and cryogenic transmission electron microscopy. This cube is the largest discrete abiological assembly that has been observed to bind guests in solution; cavity enclosure and coulombic effects appear to be crucial drivers of host–guest chemistry at this scale. The degree of cavity occupancy, however, appears less important: the largest guest studied, bound the most weakly, occupying only 11 % of the host cavity.